Analysis of Maternal Predisposing Factors with The Incidence of LBW in Central Java - Kujariningrum, Oktavia Beni; Winarni, Sri; Mawarni, Atik; Najib, Najib (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Abstract. In Central Java, the prevalence of LBW (Low Birth Weight) has increased from 4.3 (2018) to 4.7 (2019) and be the biggest cause of neonatal mortality (46.4%) and infant mortality (40.5%). The aim of this research is to analyze the relationship between quality of ANC (Antenatal Care), iron supplementation, pregnancy complications, and maternal smoking status with LBW in Central Java. This research was an analytical study used secondary data from the 2017 IDHS (Indonesian Demographic and Health Survey). The sampling design used purposive sampling.Population study was 1205 babies born in Central Java. The sample comprised 952 babies. Independent variables were the quality of ANC, iron supplementation, pregnancy complications, and maternal smoking status, with the incidence of LBW as dependent variable. Data analysis was performed by chi-square continuity correction and logistic regression. Pregnancy complications have been associated with the incidences of LBW in Central Java (p-value = 0.0001). Iron supplementation (OR = 2.474) and pregnancy complications (OR = 4.869) had an effect on the incidence of LBW in Central Java. Iron supplementation and pregnancy complications influenced the incidence of LBW in Central Java.